OLOF PETERSSON. THE ORDINARIUS: HERBERT TINGSTEN AND JÖRGEN WESTERSTÅHL - Lane, Jan-Erik (Baltic Journal of Political Science, 2017)
Swedish political scientist Olof Petersson has recently published two remarkable biographies, of Herbert Tingsten and Jörgen Westerståhl, two professors who dominated political science in Sweden during the twentieth century.[...]